Implementasi Problem Based Learning Terintegrasi TaRL terhadap Hasil Belajar Kognitif Kelas IV SD Negeri Plaosan 1 - Nainggolan, Elsima; Kusumo, Galih; Sekti Hari Purnami (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This research aims to analyze the implementation of the Problem Based Learning (PBL) learning model which is integrated with the Teaching at the Right Level (TaRL) approach on the cognitive learning outcomes of class IV students at SD Negeri Plaosan 1. The sample in this study was 28 students. Carrying out the diagnostic assessment was carried out using descriptive quantitative research and continued with One-Group Pretest-Posttest Design. The research techniques used are cognitive diagnostic tests, interviews, questionnaires, pretest-posttest, and with data analysis techniques using quantitative descriptive analysis and paired t-test. The findings show that there is an increase in cognitive learning outcomes with the high category 7.14%, the medium category 89.29%, and the low category 3.57%. These results are strengthened by the t-test value with sig 0.000 < 0.005, so it can be concluded that there is a difference in the average value before and after treatment and research show that class IV students have a diversity of characteristics and learning needs and the implementation of TaRL integrated PBL has a significant effect on students' cognitive learning outcomes. Thus, the TaRL integrated PBL model can be used as an innovation in learning with different subjects and at different grade levels.